HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI MADRASAH IBTIDAIYAH PONDOK PESANTREN QODRATULLAH LANGKAN BANYUASIN - Yusrina Yusrina (Conciencia, 2014)
Abstract:This research is motivated by the students who have high academic achievement but there are still children who are less able to control his emotions as controlling yourself in hanging out with friends, and set the mood, and less empathy equally friend.Based on the above background, which is at issue in this thesis is 1). how emotional intelligence of students in Elementary School Boarding Qodratullah ledge Banyuasin, 2). how student achievement in the subjects of Islamic religious education at Government Elementary School Boarding Qodratullah ledge Banyuasin and 3). whether there is a relationship between emotional intelligence and academic achievement of students in the subjects of Islamic religious education at Government Elementary School Boarding Qodratullah Banyuasin ledge. To answer the question in this thesis researchers used a quantitative approach. To get the data, researchers used several techniques that questionnaire as the main data used to obtain data related to students' emotional intelligence then observation, documentation and interview as supporting data in the study of emotional intelligence and academic achievement. Data analysis technique used product moment correlation.Based on the research findings, emotional intelligence were high, then when categorized emotional intelligence of students in Elementary School Qodratullah ledge moderate. As for student achievement obtained from the questionnaire and tests that were high then when categorized student achievement in Elementary School Qodratullah relatively high ledge. The relationship between emotional intelligence and academic achievement of students is very signitifikan. It can be concluded that emotional intelligence related to student achievement in Qodratullah Ledge Elementary School. Keywords: Emotional Intelligence, Learning Achievement.